Metasurface supporting broadband circular dichroism for reflected and transmitted fields simultaneously. (4th August 2020) - Amin, M; Siddiqui, O; Farhat, M
Abstract: We demonstrate significant optical activity in the near-infrared spectrum of a chiral metasurface which is designed using an array of L-shaped silver nanostructures. The far-field radiation from the plasmon-polariton surface wave currents produces combination of strong and highly dispersive orthogonal electric field components leading to the observation of broadband circular and elliptical polarization states (dichroism) for reflected and transmitted fields. Full-wave electromagnetic simulations show a linear to left hand and right hand circular polarization conversion between 200–261 THz frequency (1.15 µ m–1.5 µ m wavelength) range for reflected and transmitted fields. The structural chirality can be further enhanced by engraving another smaller L-dipole in nested configuration reaching near perfect polarization conversion efficiency. The nested L-dipole configuration supports circular polarization conversion between 262–306 THz frequency (980 nm–1.14 µ m wavelength) range. Full-wave simulations suggest clear enhancement of the surface currents with helical orientation leading to increased optical activity. The proposed optical waveplate may be utilized in polarization control applications such as optical imaging, sensing, and display components.